Micro Health Insurance Among Rural Women - Deepa V.; Sridevi M. (Integrated Journal for Research in Arts and Humanities, 2022)
The study determined the level of awareness and satisfaction with micro health insurance among rural women in the Puducherry Union territory. Using survey methods, primary data was acquired from insured members via a questionnaire. With the help of SPSS 20.0, a Chi-Square analysis was performed to determine the level of awareness and satisfaction, as well as demographic and socioeconomic characteristics. The findings imply that boosting knowledge is a key prerequisite for voluntary participation in MHI schemes, and that interactive, contextualised awareness tools might help people better understand insurance. The research indicates that the Puducherry Union Territory's microhealth insurance scheme can be an effective instrument for increasing health among rural women.